The Sigindo Panjang Ancestor of the Koto Beringin Community and His Descendants in the Incung Manuscript in Kerinci - Wijaya, Iqra Pandu; Riza, Yulfira; Hakim, Lukmanul (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
The Sigindo system is a tribal leadership or government system in Kerinci that occurred between the 13th and 14th centuries AD throughout the Kerinci region. Based on an ancient Incung script in the Malay-Kerinci language collection from Dusun Sungai Liuk, a manuscript text was found that tells about one of the Sigindos found in Kerinci, precisely in the Koto Beringin area. In the text of the manuscript, it is stated about the genealogy of the descendants of Sigindo Panjang who became the stake of the Koto Beringin country or important figures in Koto Beringin. It is known that Sigindo Panjang had three children, namely a boy named Depati Harak Pandang or Depati Sarik Padang and two girls who were named Panatih Panjang and Panatih Pandak. The descendants of Sigindo Panjang's three children, later became the stake of the Koto Beringin country, which came from the descendants of Depati Harak Pandang, numbering seven people. The seven people are said to be pegs kacin or pegs of the land in Koto Beringin, namely Hadir Mulan, Hadir Hunut, Hadir Gadang, Mangku Garang, Malin Saka, Manti Manis and Salih Mandayu. Sistem Sigindo merupakan sistem kepemimpinan atau pemerintahan kesukuan di Kerinci yang terjadi antara abad ke-13 dan 14 M di seluruh wilayah Kerinci. Berdasarkan naskah kuno beraksara Incung berbahasa Melayu-Kerinci koleksi Dusun Sungai Liuk, ditemukan teks naskah yang menceritakan tentang salah satu Sigindo yang terdapat di Kerinci, tepatnya di wilayah Koto Beringin. Dalam teks naskah disebutkan perihal silsilah anak keturunan Sigindo Panjang yang menjadi pasak negeri Koto Beringin atau tokoh-tokoh penting di Koto Beringin, diketahui bahwa Sigindo Panjang memiliki tiga orang anak yaitu yang laki-laki bernama Depati Harak Pandang atau Depati Sarik Padang dan dua perempuan yang bernama Panatih Panjang dan Panatih Pandak. Keturunan-keturunan dari ketiga anak Sigindo Panjang, kemudian menjadi pasak negeri Koto Beringin yang berasal dari keturunan Depati Harak Pandang yang berjumlah tujuh orang. Adapun tujuh orang tersebut dikatakan menjadi pasak kacin atau pasak negeri di Koto Beringin, yaitu Hadir Mulan, Hadir Hunut, Hadir Gadang, Mangku Garang, Malin Saka, Manti Manis dan Salih Mandayu.